Renewable Energy Trends and Applications - Nayeripour, Majid; Kheshti, Mostafa (IntechOpen, 2011)
Increase in electricity demand and environmental issues resulted in fast development of energy production from renewable resources. In the long term, application of RES can guarantee the ecologically sustainable energy supply. This book indicates recent trends and developments of renewable energy resources that organized in 11 chapters. It can be a source of information and basis for discussion for readers with different backgrounds.